MODEL PENGEMBANGAN KOMPETENSI PENDIDIKAN BERBASIS SPIRITUALITAS - Raudhatul Raudhatul (lembaga Sepercenter, 2024)
This study examines the integration of spirituality in educational competency development management as a holistic approach that can strengthen the quality of educators in the modern era. Spirituality is understood as transcendental values—such as sincerity, empathy, integrity, and self-awareness that can form the foundation for shaping the professional behavior of educators. Through literature study and conceptual analysis of various scientific sources, this study examines the role of spirituality in improving pedagogical, professional, social, and personality competencies. The results show that spirituality contributes significantly to improving intrinsic motivation, reflective abilities, emotional resilience, and the quality of educators' interpersonal relationships. This study also proposes a spirituality-based competency development model that includes four stages: internalization of values, self-reflection, transformation of learning practices, and integration into educational policy. This model is considered effective in creating educators who are not only technically competent but also possess moral maturity and strong character. Thus, the integration of spirituality becomes a strategic alternative in the development of more humanistic, meaningful, and sustainable educational human resources...